DOME-SHAPED MACULA IN MYOPIC EYES: Twelve-Month Follow-up. Issue 4 (April 2017) - Lorenzo, Daniel; Arias, Luis; Choudhry, Netan; Millan, Eduard; Flores, Ignacio; Rubio, Marcos J.; Cobos, Estefanía; García-Bru, Pere; Filloy, Alejandro; Caminal, Josep M.
Abstract : Purpose: To study the long-term clinical course of dome-shaped macula in myopic eyes and to evaluate treatment efficacy for subretinal fluid (SRF) as a related complication. Methods: A retrospective, single-center consecutive case series study was conducted. The authors analyzed myopic eyes with dome-shaped macula in patients who presented for evaluation of decreased vision. Dome-shaped macula was defined as a convexity of the retina-choroidal macular complex seen on spectral domain optical coherence tomography images. All patients were followed for at least 12 months (mean, 25 months). Fluorescein angiography and/or indocyanine green angiography were performed in cases with SRF to rule out choroidal neovascularization. Results: A total of 56 dome-shaped macula eyes from 36 patients were included in the study (bilateral in 55% of patients). Mean patient age was 56.9 ± 13.1 years. The mean spherical equivalent was −9.1 ± 6.0 diopters; 53% of eyes were considered highly myopic (>−6 diopters) and 47% of eyes were mildly myopic. In most cases (37 eyes; 66.1%), the dome-shaped macula was detected on vertical spectral domain optical coherence tomography scan patterns. No significant changes ( P ≥ 0.1) were observed in mean best-corrected visual acuity or mean central foveal thickness from baseline to final follow-up. Subretinal fluid was present in 29 eyes (51.8%) at baseline, with no differences in best-corrected visual acuity in eyes with and without SRF ( P ≥ 0.05). Nineteen of the 29 SRF eyes were treated: 8 underwent low-fluence photodynamic therapy, whereas 7 received bevacizumab, and 4 ranibizumab. No significant differences were found between treated and untreated SRF eyes in best-corrected visual acuity improvement ( P ≥ 0.1), or complete resolution of SRF ( P ≥ 0.1). Likewise, photodynamic therapy did not yield any significant benefit versus untreated eyes in best-corrected visual acuity or improvement of SRF. Conclusion: Dome-shaped macula is a condition associated with myopic eyes that seems to remain stable over time in terms of vision and macular profiles. It is often associated with chronic SRF, for which no effective treatment is current available. However, SRF does not seem to be a significant cause of visual impairment. Abstract : Dome-shape macula is a condition associated with myopic eyes that seems to remain stable over time in terms of vision and macular profiles. It is often associated with chronic subretinal fluid, for which no effective treatment is current available.